2019
DOI: 10.20546/ijcmas.2019.811.109
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Baby Corn Varieties under Different Levels of Fertilizers during Summer Season

Abstract: It has short growth duration and offers an intensive rotation cultivation system which is an excellent solution for promoting economic situation and alleviation of poverty especially in countries with high population problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…This might be due to increase in Phosphorus levels with wider row spacing levels led to better interception, absorption and utilization of available nutrients and soil moisture which empowered the plant to manufacture more quantities of photosynthates and accumulating enhanced sink capacity and maximum nutrient uptake by the crop. Besides, positive response of yield attributing characters such as length of cob, length of corn, cob weight and corn weight at higher levels of fertilizer dose of Phosphorus and wide spacing levels attributed to higher cob and corn yields, these results were stated in conformity with Medhi Dhabanita and Dutta Rinjumoni [8].…”
Section: Yield Attributes and Yieldsupporting
confidence: 64%
“…This might be due to increase in Phosphorus levels with wider row spacing levels led to better interception, absorption and utilization of available nutrients and soil moisture which empowered the plant to manufacture more quantities of photosynthates and accumulating enhanced sink capacity and maximum nutrient uptake by the crop. Besides, positive response of yield attributing characters such as length of cob, length of corn, cob weight and corn weight at higher levels of fertilizer dose of Phosphorus and wide spacing levels attributed to higher cob and corn yields, these results were stated in conformity with Medhi Dhabanita and Dutta Rinjumoni [8].…”
Section: Yield Attributes and Yieldsupporting
confidence: 64%
“…In a recent study by Medhi and Dutta (2019), the growth of three baby corn varieties was compared. CMVL Baby corn-2 emerged as a standout, boasting the tallest plant height at 148.61 cm, tying with G-5414.…”
Section: Effect Of Cultivars On Baby Corn Growthmentioning
confidence: 99%
“…Medhi and Dutta (2019) evaluated three cultivars under various levels of fertilizer. They reported that in G-5414 cultivar with fertilizer 105 N, 70 P 2 O 5 and 70 K 2 O kg ha -1 treatment produce maximum corn yield, fodder yield and no of cobs plant -1 .…”
mentioning
confidence: 99%